Observation of MHD Instabilities Driven by Energetic Electrons in the Large Helical Device*supported by the Grant-in-Aid for Encouragement of Scientists from the Japan Society for the Promotion of Science (No. 20656150). This work was also partly supported by the JSPS-NRF-NSFC A3 Foresight Program in the field of Plasma Physics (NSFC: No. 11261140328 and NRF: No. 2012K2A2A6000443). (April 2015) - Isobe, Mitsutaka; Ogawa, Kunihiro; Shimizu, Akihiro; Osakabe, Masaki; Kubo, Shin; Toi, K.; LHD Experiment Group
Abstract Coherent magnetic fluctuations in an acoustic range of frequency have been regularly observed in low-density (ne < 0.2×1019 m−3) plasmas with strong second harmonic electron cyclotron resonance heating (ECRH) on the Large Helical Device. Hard X-ray measurements indicated that energetic electrons are generated in these ECRH discharges. The magnetic fluctuations are suppressed in higher density discharges where energetic electrons are not present. The ECRH power modulation experiment indicated that the observed magnetohydrodynamic (MHD) mode has an acoustic nature rather than an Alfvénic nature.